Assessing the impact of contraceptive use on mental health among women of reproductive age - a systematic review - Shayesteh Jahanfar; Julie Mortazavi; Amy Lapidow; Cassandra Cu; Jude Al Abosy; Katherine Morris; Juan Camilo Becerra-Mateus; Paola Andrenacci; Marwa Badawy; Meredith Steinfeldt; Olivia Maurer; Bohang Jiang; et al. (BMC, 2024)
Abstract Background Contraceptive use is the principal method by which women avoid unintended pregnancy. An unintended pregnancy can induce long-term distress related to the medical, emotional, and social consequences of carrying that pregnancy to term. Objectives This review investigates the effects of modern contraception techniques such as birth control pills, long-acting reversible contraceptives (e.g., intrauterine devices, implants), and condoms on mental health status. Methods We searched multiple databases from inception until February 2022, with no geographical boundaries. RCTs underwent a quality assessment using the GRADE approach while the quality of observational studies was assessed using the Downs and Black scoring system. Data were analyzed through meta-analysis and relative risk and mean difference were calculated and forest plots were created for each outcome when two or more data points were eligible for analysis. Main results The total number of included studies was 43. In women without previous mental disorders, both RCTs (3 studies, SMD 0.18, 95% CI [0.02, 0.34], high quality of evidence) and cohort studies (RR 1.04 95% CI [1.03, 1.04]) detected a slight increase in the risk of depression development. In women with previous mental disorders, both RCTs (9 studies, SMD − 0.15, 95% CI [-0.30, -0.00], high quality of evidence) and cohort studies (SMD − 0.26, 95% CI [-0.37, -0.15]) detected slight protective effects of depression development. It was also noticed that HC demonstrated protective effects for anxiety in both groups (SMD − 0.20, 95% CI [-0.40, -0.01]). Conclusions Among women with pre-existing mental disorders who use hormonal contraceptives, we reported protective association with decreased depressive symptoms. However, the study also draws attention to some potential negative effects, including an increase in the risk of depression and antidepressant use among contraceptive users, a risk that is higher among women who use the hormonal IUD, implant, or patch/ring methods. Providers should select contraceptive methods taking individual aspects into account to maximize benefits and minimize risks.